Amy Sillman: the all-over - Kelly, Karen J. 1964- (Dancing Foxes Press, 2017)
Sillman's works can be categorized as abstract painting, although her abstractions repeatedly allow forms and figures to be recognized. The title of the exhibition 'the ALL-OVER' refers to a concept often used to describe abstract painting. At its most literal, it refers to the practice of completely covering the canvas, a format that resists a traditional figure/ground hierarchy. The classic example of the style is embodied by the work of the American artist Jackson Pollock, though as the influential critic Clement Greenberg pointed out, the style in fact originated with the Ukrainian-American artist Janet Sobel. Sillman adapts this 'all-over' idea, using it as the title for her exhibition, which does not feature drip paintings as such, but which updates the idea of total coverage of the canvas through mechanical means (via inkjet printing) used in combination with the gestural. Panorama, consisting of twenty-four canvases, was developed for Portikus and is here seen in its entirety for the first time. Exhibition: Portikus, Frankfurt am Main, Germany (02.07. - 11.09.2016)
Published on the occasion of the exhibition 'Amy Sillman: the ALL-OVER', on view at Portikus, Frankfurt, July 2 - September 11, 2016
Keywords: Sillman, Amy -- 1955-; Bildband; Ausstellungskatalog -- Portikus Frankfurt am Main -- 02.07.2016-11.09.2016 -- Frankfurt am Main